Analisis Administrasi Pelatihan Karyawan di PT INKA (Persero) - Kurnia Sari, Deva May; Fiernaningsih, Nilawati (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
Administration plays a crucial role in ensuring the succes of an organization. In simple terms, administration is a process that includes planning, organizing, controling, and supervising various activities to achieve organizational goals effectively and efficiently. This study aims to analyze employee training administration at PT INKA (Persero). The research uses a qualitative method with a descriptive approach, involving data collection through interviews, observation, and documentation. The result show that the administration of employee training at PT INKA (Persero) still faces challenges, mainly due to the lack of awareness among some employees, about the importance of organiizng training document properly. Moreover, imporevemnts are needed in the areas of record-keeping, documentation, and traininf data management to ensure a more systmatic and structured approach.